Politics and Public Policy in Kenya and Tanzania - MARTOYO, SUSILO (Praeger Publishers, 1979)
Kenya and Tanzania. Two East African countries of common culture, history, and ethnic origin with two diverse concepts of development. To what extent have the countries fulfilled these conceptions, what are the costs, and what lessons have been learned? Joel D. Barkan presents and examination of the Kenyan and Tanzanian experience which assesses each country's performance within the context of the third world. A collection of comparative essays that explore different aspects of public policy, this volume illustrates both countries' approaches to urban and rural development, education, and foreign relations, including their potentials of power and regional diplomacy